The analysis of the modern financial and non-financial aspects of employees 'rewards - Dickson Mdhlalose (SSRN, 2025)
Organisations view employee rewards and innovative performance as the cornerstone for sustained competitive advantage. This study primarily analyses modern financial and non-financial employee rewards across municipal organisations. The fundamental problem discovered in this study is that in the public sector, employee rewards and innovation performance have yet to progress in parallel with time. The public sector still uses traditional rewards, thus demotivating employees' morale and killing innovative performance. This study used mixed methods techniques, surveys, research interview questions, and document reviews. Survey data was analysed using both descriptive and inferential statistics. The sample included three hundred employees, and a simple random sampling technique was used to select each population element. For interviews, data analysis employed thematic analysis and content analysis methods. The sample included twelve employees, and a haphazard convenience sampling technique was used to select each population element. The researcher used reputable sources for the document review to collect thoughts and facts. The municipalities do not have a modern total reward system, and their rewards are outdated and inconclusive. The municipalities have a reward policy; however, employees are not informed about it. The municipalities ignore employees' needs, and the culture is neither individualistic nor collectivistic since the municipalities practice an autocratic management style. This study confirmed that engagement is a crucial psychological factor in reward systems and innovative behaviours by showing that non-financial (intrinsic) rewards greatly increase employee engagement, and this consequently mediates the interaction between rewards and innovation. Cultures that value individualism and collectivism have an impact on participation and may have an impact on innovation. Indirectly, employee engagement is highly predicted by how innovation is seen and measured, highlighting the importance of creating a climate that supports innovation in maintaining staff motivation and output.
Keywords: J33; M52; M54; O31; H83; 330